Yield and economics as influenced by omission and addition of technologies from recommended soybean production technologies: YIELD AND ECONOMICS AS INFLUENCED BY RECOMMENDED SOYBEAN PRODUCTION TECHNOLOGIES - R K VERMA; N RAGHAVENDRA; S D BILLORE; A RAMESH; NIKHILESH PANDYA; NITA KHANDEKAR (Journal of Oilseeds Research, 2024)
The field experiment was conducted during kharif seasons of 2017 and 2018 to study the effect of deletion and addition of different agronomic practices from recommended package of practices on yield attributes and yield of soybean. The additional use of micronutrients (Zn, B and Mo) and secondary nutrient sulphur (S) along with recommended package of practices(RPP)showed significant positive effect on plant height, pods per plants, yields and harvest index. On pooled basis, the addition of micronutrients (Zn, B and Mo) and secondary nutrient sulphur as soil application with RPP increased the yield by 6.0 and 3.21% as compared to RPP, respectively. On the contrary, the deletion of any recommended practice from the RPP reduced the yield by 1.14 to 71.69% as compared to RPP. Similarly, the addition of micronutrients and secondary nutrients with RPP recorded higher harvest index as compared to deletion of individual recommended practice. Economics point of view, all the treatments differ significantly among themselves in respect to the cost of cultivation, significantly the highest cost of cultivation was associated with additional use of micronutrients (Zn, B and Mo) with RPP and lowest with control. Significantly the highest net returns were registered with RPP + Zn, B, Mo application and remained statistical identical with RPP + S application, RPP alone, 50% RDF (recommended dose of fertilizers) as basal + 2% urea spray at pod initiation stage and RPP + narrow row spacing (30 cm). In case of B: C ratio, significantly the highest B:C ratio was recoded with omission of RDF treatment and remained statistical identical with control treatment followed by 50% RDF as basal + 2% urea spray at pod initiation. Furthermore, when comparing yields and economics (except B:C ratio) of all the treatments with RPP in terms of positive and negative effect, the differential yields and economics both were positive with additional use of micro and secondary nutrients. Similarly, the negative trend was observed with the deletion of any practice from RPP except in case of 50% RDF + 2% urea spray where the yield showed negative trend and net income showed positive trend. Moreover, the highest positive partial factor productivity (PFP) registered with omission of RDF followed by control and then 50% RDF as basal + 2% urea spray. Whereas, other treatments exhibited negative trend in term of PFP the lowest negative values were registered with RPP + Zn, B, Mo and RPP + 25 kg S /ha.